Time Reveals the Truth! What Treatments for COVID-19 Were Quickly Abandoned, and Which Methods, Contrary to Popular Belief, Are Still Flourishing? - Joseph John Bevelacqua; Abdolkarim Ghadimi Moghadam; Seyed Alireza Mortazavi; Abdollah Jafarzadeh; Masoud Haghani; Azim Kaveh-Ahangar; Ali Ghadimi-Moghadam (Journal of Biomedical Physics and Engineering)
During the early days of the COVID-19 pandemic, low dose radiation therapy (LDRT) was proposed as a potentially effective treatment method. To minimize potential toxicity, the initial treatment approach involved a few mGy of adapting radiation followed by a single 250 mGy whole lung challenging dose. However, antiviral drugs were also introduced as a promising treatment option, which were thought to have the potential to revolutionize the management of the crisis. Despite early warnings, many physicians did not fully consider the key point that, in contrast with LDRT, antiviral drug treatments can result in strong selective pressure on the virus. This can lead to the emergence of new SARS-CoV-2 variants, a phenomenon that can have serious global consequences. After more than two years, the truth has been revealed: the WHO Guideline Development Group has advised against the use of remdesivir, a widely used antiviral medication, for COVID-19. Meanwhile, a growing body of evidence suggests that LDRT can be a promising, low-risk approach for avoiding or delaying invasive respiratory support in COVID-19 patients. Although there is substantial supporting documentation, more high-quality, controlled, and randomized double-blind clinical trials are needed to further investigate the efficacy and potential therapeutic mechanisms of LDRT for COVID-19.